Malignant Melanoma of the Urethra: A Rare Histologic Subdivision of Vulvar Cancer with a Poor Prognosis - Veronika Günther; I. Alkatout; C. Lez; S. Altarac; R. Fures; H. Cupic; Z. Persec; Z. Hrgovic; C. Mundhenke (Hindawi Limited, 2012)
Malignant melanoma of the urethra is a rare tumour that is difficult to diagnose and treat, resulting in a poor prognosis. In this paper, we present the case of a 65-year-old woman who was referred to a gynaecologist because of a urethral mass that mimicked a caruncle. The tumour was removed by local excision, and a pathological analysis revealed a malignant melanoma. Distal urethrectomy was performed after three months with no evidence of residual tumour. There was no evidence of disease at a six-year followup. In this paper, we compare the epidemiology, treatment, staging, and prognosis of vulvar cancer in general to malignant melanoma of the vulva in particular.